A Study on the "Dual Disconnection" Problem Between Theory and Practice in Vocational Education Under High-Quality Development - Chen Haiting (Journal of Exploration of Vocational Education, 2025)
Abstract:With the high-quality development of China's economy, vocational education, as a crucial pathway for cultivating skilled talents, requires an effective integration of theory and practice. Meanwhile, high-quality development has become a key direction and goal for deepening reforms in China’s vocational education in the new era. However, in the process of vocational education development, there exists a "dual disconnection" problem, where theory and practice are fragmented and mutually detached. This issue manifests as a disjunction between educational theories and the actual needs of industries, making it difficult for students to apply their acquired knowledge flexibly in real work settings. Through an in-depth analysis of the current state of vocational education theory and practice, this paper identifies the critical gaps within the vocational education system. Furthermore, it explores the impact of these issues on the quality of vocational education and proposes a series of targeted solutions. Guided by a balanced and comprehensive strategic perspective, this study aims to systematically advance the development of vocational education, fundamentally enhancing its overall quality to better meet the dual demands of socioeconomic progress and individual student development.